EVALUATION OF OCCUPATIONAL SAFETY AND HEALTH IN PT PANTJA SIMPATI - Ahmad Faqih Solansa; Hendra Nanang; M Sudiyamto (Politeknik Negeri Media Kreatif, 2021)
Every production process in a company is inseparable from all the dangers of disease and occupational accidents for workers. So in a company it is necessary to implement occupational safety and health in order to reduce and prevent occupational diseases and accidents. In carrying out occupational safety and health at PT Pantja Simpati, PT Pantja Simpati has several problems that can cause illness and work accidents such as unavailability of personal protective equipment, non-functioning air vents, employees smoking in the production room, employees drinking in the production section. part. areas, fire fighting equipment lacks lighting, damaged ceilings or roofs, untidy cables, and slippery production floors. Ways to avoid work accidents such as providing PPE and APAR, repairing damaged equipment, and taking firm action against workers. From the problems found, the implementation of occupational safety and health at PT Pantja Simpati is still not good.Keywords— Occupational Safety and Health, 5W+1H